A 9,9-di-n-octylfluorene copolymer and its preparation method and application
By using the anicyclic carbene palladium complex to prepare 9,9-di-octylfluorene copolymer as the hole transport layer material for perovskite solar cells, the problem of existing materials being difficult to improve the performance of solar cells at the same time is solved, efficient and stable photoelectric conversion efficiency is achieved, and the toxicity problem of phosphine ligands is avoided.
Patent Information
- Application Number
- CN202510012626.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The hole transport layer materials of existing perovskite solar cells are difficult to increase the Voc, Jsc and FF values simultaneously, thus limiting the PCE value of perovskite solar cells. In addition, the phosphine ligands in traditional catalysts are highly toxic and sensitive to the environment, and the preparation conditions are harsh.
The 9,9-di-octylfluorene copolymer was prepared by catalyzed with azo-heterocyclic carbene palladium complex, which was used to prepare the hole transport layer of perovskite solar cells. The hole transport layer was prepared by mixing it with PTAA to improve the photoelectric conversion efficiency of perovskite solar cells.
The Voc, Jsc and FF values of perovskite solar cells were increased, thereby significantly increasing the PCE value of perovskite solar cells and avoiding the toxicity problem of phosphine ligand catalysts.
Smart Images

Figure CN119409951B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic photoelectric polymer materials, and in particular relates to a 9,9-di-n-octylfluorene copolymer and a preparation method and application thereof. Background Art
[0002] Perovskite solar cells are a type of solar cell that has emerged in recent years and has great development prospects. They have the advantages of high photoelectric conversion efficiency, simple production, and low cost. Photoelectric conversion efficiency is one of the important performance indicators for measuring the quality of perovskite solar cells. At present, there are two main technical means to improve the photoelectric conversion efficiency of perovskite solar cells. One is to optimize the structure or adjust the morphology of each layer of the perovskite solar cell to optimize the interface performance; the other is to change the material composition of the perovskite solar cell and develop hole transport layer, perovskite absorption layer or electron transport layer materials with better performance.
[0003] The structure of perovskite solar cells includes a substrate layer, an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, and a metal back electrode. Among them, in perovskite solar cells, the hole transport layer material plays an important role in the extraction and transport of carriers, as well as in inhibiting carrier recombination and protecting the perovskite layer. Therefore, the development of efficient and stable hole transport materials is a research hotspot in the field of perovskite solar cells.
[0004] Common hole transport layer materials mainly include organic or inorganic materials such as nickel oxide, cuprous thiocyanate, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] and poly(3,4-ethylenedioxythiophene), but these materials are difficult to simultaneously improve the Voc, Jsc and FF values of perovskite solar cells, thereby improving the PCE value of perovskite solar cells. In addition, palladium / phosphine ligand catalysis is often used to prepare hole transport layer materials, but phosphine ligands are not only highly toxic, but also extremely sensitive to air and water vapor, making the conditions for the catalytic reaction involving phosphine ligands extremely harsh. Therefore, it is an urgent problem to provide a method for synthesizing hole transport layer materials without using phosphine ligands and to provide hole transport layer materials that are conducive to improving the PCE value of perovskite solar cells. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, a 9,9-di-n-octylfluorene copolymer and a preparation method and application thereof are provided. The present invention provides a 9,9-di-n-octylfluorene copolymer for preparing a perovskite solar cell, which is beneficial to improving the Voc, Jsc and FF values of the perovskite solar cell, thereby improving the PCE value of the perovskite solar cell; and the 9,9-di-n-octylfluorene copolymer is prepared by catalysis of a nitrogen heterocyclic carbene palladium complex, which has the advantage of high catalytic efficiency, and can obtain a high molecular weight and narrow distribution 9,9-di-n-octylfluorene copolymer, thereby overcoming the problems of high toxicity of phosphine ligand catalysts.
[0006] The object of the present invention is to provide a 9,9-di-n-octylfluorene copolymer, the structure of which is shown in Formula I:
[0007]
[0008] Formula I;
[0009] The number average molecular weight Mn of the 9,9-di-n-octylfluorene copolymer is 18.6-27.2 kDa, and the molecular weight distribution PDI is 1.9-3.0.
[0010] Another object of the present invention is to provide a method for preparing the 9,9-di-n-octylfluorene copolymer, comprising the following steps:
[0011] Under the action of a nitrogen heterocyclic carbene palladium complex and an organic base, 2,7-dichloro-9,9-dioctylfluorene and 9-(1-octylnonyl)carbazole-2,7-bis(boronic acid pinacol ester) react to obtain a 9,9-dioctylfluorene copolymer;
[0012] The structure of the nitrogen heterocyclic carbene palladium complex is shown in Formula II:
[0013]
[0014] Formula II.
[0015] In some embodiments of the present invention, the molar ratio of the 2,7-dichloro-9,9-dioctylfluorene, 9-(1-octylnonyl)carbazole-2,7-bis(boronic acid pinacol ester) and the nitrogen heterocyclic carbene palladium complex is 1:1:0.005-0.015.
[0016] In some embodiments of the present invention, the organic base is selected from potassium tert-butoxide.
[0017] In some embodiments of the present invention, the molar ratio of the organic base to 2,7-dichloro-9,9-dioctylfluorene is 3-5:1.
[0018] In some embodiments of the present invention, the reaction temperature is 60-100° C. and the reaction time is 8-16 hours.
[0019] In some embodiments of the present invention, the reaction further comprises a solvent, and the solvent is selected from a mixed solvent of tetrahydrofuran and water.
[0020] In some embodiments of the present invention, the volume ratio of tetrahydrofuran to water is 2-4:1.
[0021] In some embodiments of the present invention, after the reaction is completed, a purification step is further included.
[0022] Another object of the present invention is to provide the use of the 9,9-di-n-octylfluorene copolymer or the 9,9-di-n-octylfluorene copolymer prepared by the preparation method of the 9,9-di-n-octylfluorene copolymer in the preparation of perovskite solar cells.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention adopts nitrogen heterocyclic carbene palladium complex as catalyst to prepare 9,9-di-n-octylfluorene copolymer, which has the advantage of high catalytic efficiency and can obtain high molecular weight and narrow distribution 9,9-di-n-octylfluorene copolymer, thus overcoming the problem of high toxicity of phosphine ligand catalyst.
[0025] (2) The 9,9-di-n-octylfluorene copolymer prepared by the present invention is used to prepare perovskite solar cells, which is beneficial to improving the Voc, Jsc and FF values of the perovskite solar cells, thereby improving the PCE value of the perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the H NMR spectrum of the 9,9-di-n-octylfluorene copolymer prepared in Example 2. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0028] All raw materials of the present invention are conventionally commercially available.
[0029] The PTAA used in Examples 5-7 and Comparative Examples 2-3 is derived from Example 2 of CN118978672A.
[0030] The structural formula of the nitrogen heterocyclic carbene palladium complex C1 of the present invention is as follows:
[0031] .
[0032] Example 1
[0033] This embodiment provides a nitrogen heterocyclic carbene palladium complex C1, and the preparation method thereof comprises the following steps:
[0034] S1. 2,6-diisopropylaniline (4.4mmol), 4,7-di-tert-butylacenaphthenequinone (2mmol), and anhydrous zinc chloride (4.6mmol) were added to a 100 ml side-mouth bottle in sequence, and 50 ml of glacial acetic acid was added as solvent. The reaction was carried out at 120°C under N2 protection and reflux for 5 hours. After the reaction was completed, the solution was cooled to room temperature. An orange-yellow solid was generated in the solution. The solution was filtered and the filter cake was rinsed with glacial acetic acid for several times to remove the unreacted raw materials. The solid obtained by filtration was dried and dissolved in dichloromethane. The solution was dezincified with 100 mL of potassium oxalate aqueous solution (4.6 g / L). After stirring for 5 hours, the white zinc salt was removed by filtration. The remaining organic layer was extracted with water for several times. After the solvent was removed by vacuum distillation, the solution was recrystallized with (dichloromethane / n-hexane) to obtain orange-yellow crystals, i.e., diimine compound D1, with a yield of 68%;
[0035] S2. Weigh the diimine compound D1 (1.0 mmol) into a 25 ml eggplant-shaped flask, add 3-4 ml of chloromethyl ether to dissolve it, react at 100 ° C for 24 h under N2 protection, and recrystallize from dichloromethane / petroleum ether to obtain compound E1 with a yield of 48%;
[0036] Weigh compound E1 (0.2 mmol), palladium chloride (0.22 mmol), potassium carbonate (2 mmol), and 3-chloropyridine (1.2 mmol) into a reaction bottle, add 4 ml of acetone, and react at 60°C for 8 h. After the reaction, extract with water to remove excess potassium carbonate, and recrystallize the organic layer with dichloromethane / n-hexane to obtain a yellow solid, i.e., nitrogen heterocyclic carbene palladium complex C1, with a yield of 57%;
[0037] The NMR data of the nitrogen heterocyclic carbene palladium complex C1 are as follows:
[0038] 1 H NMR (400 MHz, CDCl3) δ 8.70 (d, J = 2.3 Hz, 1H), 8.62 (dd, J = 5.5,1.1 Hz, 1H), 7.64 (d, J = 12.3 Hz, 4H), 7.57 (d, J = 8.3 Hz, 1H), 7.49 (d, J= 7.8 Hz, 4H), 7.10 (dd, J = 8.2, 5.6 Hz, 1H), 6.81 (s, 2H), 3.39 (t, J =13.4, 6.7 Hz, 4H), 1.46 (d, J = 6.6 Hz, 12H), 1.24 (s, 18H), 0.91 (d, J = 6.8Hz, 12H).
[0039] 13C NMR (101 MHz, CDCl3) δ 157.96, 150.81, 149.74, 147.42, 140.81,137.55, 133.99, 132.00, 130.82, 128.92, 126.41, 125.68, 124.79, 124.44,122.66, 120.90, 35.45, 31.18, 29.01, 25.83, 24.39.
[0040] Example 2
[0041] This embodiment provides a 9,9-di-n-octylfluorene copolymer, and the preparation method thereof comprises the following steps:
[0042] Under nitrogen protection, 2,7-dichloro-9,9-dioctylfluorene (1.0 mmol), 9-(1-octylnonyl)carbazole-2,7-bis(boronic acid pinacol ester) (1.0 mmol), potassium tert-butoxide (4.0 mmol), nitrogen heterocyclic carbene palladium complex C1 (0.01 mmol) and 10 mL of tetrahydrofuran / water (3:1) were added into a crimped round-bottom microwave reaction tube as a solvent, and the mixture was stirred at 80°C for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, and the polymer was precipitated with methanol, washed several times, dried, and weighed to obtain a 9,9-di-n-octylfluorene copolymer with a yield of 67%. The 9,9-di-n-octylfluorene copolymer was characterized by nuclear magnetic resonance and GPC. The number average molecular weight Mn of the 9,9-di-n-octylfluorene copolymer was 23.1 kDa, and the molecular weight distribution PDI was 2.4.
[0043] The structure of the 9,9-di-n-octylfluorene copolymer is shown below:
[0044] .
[0045] Example 3
[0046] This embodiment provides a 9,9-di-n-octylfluorene copolymer, and the preparation method thereof comprises the following steps:
[0047] Under nitrogen protection, 2,7-dichloro-9,9-dioctylfluorene (1.0 mmol), 9-(1-octylnonyl)carbazole-2,7-bis(boronic acid pinacol ester) (1.0 mmol), potassium tert-butoxide (3.0 mmol), nitrogen heterocyclic carbene palladium complex C1 (0.005 mmol) and 10 mL of tetrahydrofuran / water (3:1) were added into a crimped round-bottom microwave reaction tube as a solvent, and the mixture was stirred at 60° C. for 16 hours. After the reaction was completed, the mixture was cooled to room temperature, and the polymer was precipitated with methanol, washed several times, dried, and weighed to obtain a 9,9-di-n-octylfluorene copolymer with a yield of 59%. The 9,9-di-n-octylfluorene copolymer was characterized by GPC, and the number average molecular weight Mn of the 9,9-di-n-octylfluorene copolymer was 18.6 kDa, and the molecular weight distribution PDI was 3.0.
[0048] The structure of the 9,9-di-n-octylfluorene copolymer is shown below:
[0049] .
[0050] Example 4
[0051] This embodiment provides a 9,9-di-n-octylfluorene copolymer, and the preparation method thereof comprises the following steps:
[0052] Under nitrogen protection, 2,7-dichloro-9,9-dioctylfluorene (1.0 mmol), 9-(1-octylnonyl)carbazole-2,7-bis(boronic acid pinacol ester) (1.0 mmol), potassium tert-butoxide (5.0 mmol), nitrogen heterocyclic carbene palladium complex C1 (0.015 mmol) and 10 mL of tetrahydrofuran / water (3:1) as solvent were added to a crimped round-bottom microwave reaction tube, and the mixture was stirred at 100° C. for 8 hours. After the reaction was completed, it was cooled to room temperature, and the polymer was precipitated with methanol, washed several times, dried, and weighed to obtain 9,9-di-n-octylfluorene copolymer with a yield of 71%. The 9,9-di-n-octylfluorene copolymer was characterized by GPC, and the number average molecular weight Mn of the 9,9-di-n-octylfluorene copolymer was 27.2 kDa, and the molecular weight distribution PDI was 1.9.
[0053] The structure of the 9,9-di-n-octylfluorene copolymer is shown below:
[0054] .
[0055] Comparative Example 1
[0056] This embodiment provides a 9,9-di-n-octylfluorene copolymer, and the preparation method thereof comprises the following steps:
[0057] The difference from Example 2 is that the nitrogen heterocyclic carbene palladium complex is replaced by Pd(PPh3)4, and the remaining steps are the same as Example 2, and a 9,9-di-n-octylfluorene copolymer is obtained with a yield of 49%; the 9,9-di-n-octylfluorene copolymer is characterized by GPC, and the number average molecular weight Mn of the 9,9-di-n-octylfluorene copolymer is 9.7 kDa, and the molecular weight distribution PDI is 2.6;
[0058] The structure of the 9,9-di-n-octylfluorene copolymer is shown below:
[0059] .
[0060] Example 5
[0061] This embodiment provides a pin-type perovskite solar cell, wherein the specific cell structure is ITO / 9,9-di-n-octylfluorene copolymer: PTAA / perovskite active layer / PCBM / BCP / Ag, and the preparation method thereof comprises the following steps:
[0062] (1) Cleaning of the transparent substrate layer: First, take out the ITO transparent conductive glass, tear off the plastic protective film on the surface, and first use detergent to gently wipe the surface oil and dirt, and then ultrasonically clean it in a 0.2wt% detergent aqueous solution, deionized water, and isopropanol for 15 minutes respectively. Finally, use nitrogen to blow dry the isopropanol on the ITO surface and put it in a box for later use.
[0063] (2) Deposition of hole transport layer: PTAA and the 9,9-di-n-octylfluorene copolymer prepared in Example 2 were prepared into a 2.5 mg / mL precursor solution, the mass ratio of PTAA and the 9,9-di-n-octylfluorene copolymer prepared in Example 2 was 1.5:1, the solvent was chlorobenzene, the cleaned ITO was first placed in an ultraviolet ozone cleaner for surface hydrophilic treatment, and then the precursor solution was sucked out with a pipette to evenly cover the ITO surface, and then coated on the surface by a scraper coating process.
[0064] (3) Preparation of wetting layer: The purchased aluminum oxide nanoparticle (<50 nm) dispersion (20%) was mixed with isopropanol at a volume ratio of 1:50 (aluminum oxide dispersion: isopropanol) to prepare an aluminum oxide precursor solution. The prepared aluminum oxide precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole transport layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).
[0065] (4) Preparation of perovskite active layer: The FAPbI3 system perovskite precursor solution (1000 rpm / min, 3s; 5000 rpm / min, 30s, 100 μL chlorobenzene was added as anti-solvent at 21s) was aspirated with a pipette and evenly covered on the surface of the wetting layer to form a perovskite active layer, and then annealed on a hot stage at 100°C for 30-60 min.
[0066] (5) Deposition of electron transport layer: Weigh 20 mg of PCBM and add 1 mL of chlorobenzene to prepare the precursor solution of the electron transport layer. The electron transport layer precursor solution was deposited on the surface of the perovskite active layer by spin coating (500 rpm / min, 3 s; 2500 rpm / min, 20 s).
[0067] (6) Deposition of hole blocking layer: 8 mg of BCP was weighed and 16 mL of isopropanol was added to prepare a precursor solution. The prepared precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole blocking layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).
[0068] (7) Deposition of metal electrode layer: A 100 nm thick Ag film was thermally evaporated under high vacuum at an evaporation rate of 0.3 Å / s for 20 nm and then deposited on the surface of the hole blocking layer at 1 Å / s to a thickness of 100 nm.
[0069] Example 6
[0070] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 5 only in that: in point (2) of Embodiment 5, "the 9,9-di-n-octylfluorene copolymer prepared in Embodiment 2" is replaced by "the 9,9-di-n-octylfluorene copolymer prepared in Embodiment 3", and the remaining steps are the same as in Embodiment 5.
[0071] Example 7
[0072] This embodiment provides a pin-type perovskite solar cell, which differs from Embodiment 5 only in that: in point (2) of Embodiment 5, "the 9,9-di-n-octylfluorene copolymer prepared in Embodiment 2" is replaced by "the 9,9-di-n-octylfluorene copolymer prepared in Embodiment 4", and the remaining steps are the same as those in Embodiment 5.
[0073] Comparative Example 2
[0074] This comparative example provides a pin-type perovskite solar cell, which differs from Example 5 only in that: in point (2) of Example 5, "the 9,9-di-n-octylfluorene copolymer prepared in Example 2" is replaced by "the 9,9-di-n-octylfluorene copolymer prepared in Comparative Example 1", and the remaining steps are the same as Example 5.
[0075] Comparative Example 3
[0076] This comparative example provides a pin-type perovskite solar cell, which differs from Example 5 only in that: the "PTAA and the 9,9-di-n-octylfluorene copolymer prepared in Example 2 are configured into a 2.5 mg / mL precursor solution, and the mass ratio of PTAA and the 9,9-di-n-octylfluorene copolymer prepared in Example 2 is 1.5:1" in point (2) of Example 5 is replaced by "PTAA is configured into a 2.5 mg / mL precursor solution", and the remaining steps are the same as Example 5.
[0077] The performance of the pin-type perovskite solar cells of Examples 5 to 7 and Comparative Examples 2 to 3 was tested. The test method is as follows. The results are shown in Table 1.
[0078] The JV characteristic curve of the device was measured using a Keithley 2440 light source under a simulated AM1.5G spectrum.
[0079] The light intensity was calibrated using a solar simulator (Newport, 91160) from NREL using a standard silicon solar cell device. The effective measurement area was 0.07 cm 2 , under reverse and forward bias scans, the scan rate was 100mV / s and the bias range was from -0.2V to 1.2V.
[0080] Table 1. Performance of perovskite solar cells of Examples 5-7 and Comparative Examples 2-3.
[0081] sample Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Example 5 1.13 22.21 79.32 19.91 Example 6 1.14 19.93 76.07 17.28 Example 7 1.15 24.86 83.43 23.85 Comparative Example 2 0.89 18.02 60.61 9.72 Comparative Example 3 0.95 19.37 75.38 13.87
[0082] As can be seen from Table 1, the 9,9-di-n-octylfluorene copolymer prepared in Examples 5 to 7 of the present invention is mixed with PTAA to prepare a hole transport layer, which is used to prepare a perovskite solar cell, which is beneficial to improve the Voc, Jsc and FF values of the perovskite solar cell, thereby improving the PCE value of the perovskite solar cell.
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that after reading the specification of this application, the technicians can still modify or replace the specific implementation mode of the present invention with equivalents, but these modifications or changes do not deviate from the scope of protection of the pending claims of the present application.
Claims
1. A 9,9-di-n-octylfluorene copolymer, characterized in that: The structure of the 9,9-di-n-octylfluorene copolymer is shown in formula (I): Formula (I) The number average molecular weight Mn of the 9,9-di-n-octylfluorene copolymer is 23.1-27.2 kDa, and the molecular weight distribution PDI is 1.9-3.
0.
2. The method for preparing the 9,9-di-n-octylfluorene copolymer according to claim 1, characterized in that: The steps include: Under the action of a nitrogen heterocyclic carbene palladium complex and an organic base, 2,7-dichloro-9,9-dioctylfluorene and 9-(1-octylnonyl)carbazole-2,7-bis(boronic acid pinacol ester) react to obtain a 9,9-dioctylfluorene copolymer. The structure of the nitrogen heterocyclic carbene palladium complex is shown in formula (I): Formula (I).
3. The method for preparing the 9,9-di-n-octylfluorene copolymer according to claim 2, characterized in that: The molar ratio of the 2,7-dichloro-9,9-dioctylfluorene, 9-(1-octylnonyl)carbazole-2,7-bis(boric acid pinacol ester) and the nitrogen heterocyclic carbene palladium complex is 1:1:0.005-0.
015.
4. The method for preparing the 9,9-di-n-octylfluorene copolymer according to claim 2, characterized in that: The organic base is selected from potassium tert-butoxide.
5. The method for preparing the 9,9-di-n-octylfluorene copolymer according to claim 2, characterized in that: The molar ratio of the organic base to 2,7-dichloro-9,9-dioctylfluorene is 3-5:
1.
6. The method for preparing the 9,9-di-n-octylfluorene copolymer according to claim 2, characterized in that: The reaction temperature is 60-100° C. and the reaction time is 8-16 hours.
7. The method for preparing the 9,9-di-n-octylfluorene copolymer according to claim 2, characterized in that: The reaction further comprises a solvent, and the solvent is selected from a mixed solvent of tetrahydrofuran and water.
8. The method for preparing the 9,9-di-n-octylfluorene copolymer according to claim 7, characterized in that: The volume ratio of tetrahydrofuran to water is 2-4:
1.
9. The method for preparing the 9,9-di-n-octylfluorene copolymer according to claim 2, characterized in that: After the reaction is completed, a purification step is also included.
10. Use of the 9,9-di-n-octylfluorene copolymer according to claim 1 or the 9,9-di-n-octylfluorene copolymer prepared by the preparation method of the 9,9-di-n-octylfluorene copolymer according to any one of claims 2 to 9 in the preparation of perovskite solar cells.
Citation Information
Patent Citations
Preparation method of PTAA
CN118978672A